The joy of science - Hazen, Robert M., 1948-; Burgstaller, Andreas; Teaching Company (Chantilly, VA : The Great Courses / The Teaching Co., 2001)
English novelist and scientist C. P. Snow classed certain scientific ideas with the works of Shakespeare as things every educated person should know. The lectures in this series explore the fundamental discoveries and principles of the physical and biological sciences--physics, genetics, biology, astronomy, chemistry, meteorology, thermodynamics, and more--providing a comprehensive and integrated introduction to all of science. The Joy of Science, through enhancing an understanding of the physical world, offers a source of endless wonder and intellectual joy.
Part V. Disc 9. Lecture forty nine The discovery of DNA ; Lecture fifty The genetic code ; Lecture fifty one Reading the genetic code ; Lecture fifty two Genetic engineering ; Lecture fifty three Cancer and other genetic diseases ; Lecture fifty four The chemical evolution of life -- Disc 10. Lecture fifty five Biological evolution: A unifying theme of biology ; Lecture fifty six The fact of evolution: The fossil record ; Lecture fifty seven Charles Darwin and the theory of natural selection ; Lecture fifty eight Ecosystems and the law of unintended consequences ; Lecture fifty nine The ozone hole, acid rain, and the greenhouse effect ; Lecture sixty Science: The endless frontier.
DVD.
Sixty lectures of thirty minutes each by Robert M. Hazen, Clarence Robinson Professor of Earth Science at George Mason University, and researcher at the Geophysical Laboratory of the Carnegie Institution of Washington.
Producer, Andreas Burgstaller ; editor, Sal Rodriguez ; content supervisor, Ann Waigand.
Course guidebook includes professor biography, statement of course scope, lecture outlines and notes, timeline, glossary, biographical notes, and bibliography (p. 290-296).
Keywords: Newton, Isaac, -- 1642-1727.; Bohr, Niels, -- 1885-1962.; Hubble, Edwin, -- 1889-1953.; Mendel, Gregor, -- 1822-1884.; Darwin, Charles, -- 1809-1882.; Science; Science -- History; Science -- Methodology; Cosmology; Motion; Gravity; Thermodynamics; Entropy; Magnetism; Electricity; Electromagnetism; Atoms; Relativity (Physics); Chemistry; Standard model (Nuclear physics); Astronomy; Matter; Matter -- Properties; Solar system; Earth (Planet); Earth sciences; Hydrologic cycle; Life (Biology); DNA; Genetics; Evolution (Biology); Natural selection; Biotic communities; Greenhouse effect, Atmospheric; Global warming